PENGARUH PEMAKAIAN BEBERAPA CAMPURAN BAHAN BAKAR TERHADAP EMISI GAS BUANG MOTOR BENSIN 4 TAK - Muhajir, Khairul (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
This study aims to discover the exhaust gas emission effect in the combustion chamber of four strokes spark ignition engine taking place at using of ethanol and pertamax fuel at combustion process and exit at the air. The research was conducted at using of ethanol and pertamax fuel in the four strokes of spark ignition engine at KIA CARNIVAL car at the amospheric condition ( 27o C – 30o C ).Exhaust gas emission producted from combustion process the so called poluttant result from engine with premium fuel as (HC,CO,CO2,O2,NOx). Among the cause of incomplete combustion is the poor of oxygen, so in order not to be discover the dangerous exhaust gas emission, the ethanol added at the fuel mixture.This study analysed the effect of athanol added to pertamax fuel mixture with exhaust gas emission. The methode of study with comparing pure pertamax fuel and ethanol pertamax fuel mixture with concentred of 9 % and 16.6 %, at the engine rpm speed of 1000, 2000, 3000 and 4000. and used the exhaust gas emission measurement with the ultra gas analyser.The result of this study show there are exhaust gas emission decrease at every ethanol added in to the pertamax fuel mixture, and there are also increase of fuel to air ratio. The ethanol fuel helps the combustion process because there are oxygen (O2) in the ethanol fuel, so that the ethanol fuel could be the alternative of fuel to decrease the dangerous of exhaust gas emission and to increase the octane number whatever needs at the fuel car engine with grade capacity.